Eucalypts for wood production - Hillis, W. E.; Brown, A. G. (Alan Gordon), 1931- (Commonwealth Scientific and Industrial Research Organization, Australia, 1978)
"A tribute to Stanley A. Clarke and Maxwell R. Jacobx ..."